Biomimetic cell membrane decorated ZIF‐8 nanocarriers with IR‐780 and doxorubicin loading for multiple myeloma treatment - Guangtao Gao; Junyi Che; Peipei Xu; Bing Chen; Yuanjin Zhao (Aggregate)
Abstract Several therapeutic drugs including heptamethine cyanine dye (IR‐780), doxorubicin (DOX), and others have exhibited positive outcomes in the treatment of multiple myeloma (MM). However, curing MM is still hampered by undesired off‐target effects and uncontrolled release of the therapeutics. Herein, we present novel MM‐mimicking nanocarriers by integration of DOX, IR‐780, and MM cell membrane with zeolitic imidazolate framework‐8 (ZIF‐8) nanoparticles (D/INPs@CM) for MM treatment. The nanocarriers were fabricated by co‐loading DOX and IR‐780 into ZIF‐8 and further coated with the cell membrane. After intravenous injection, the D/INPs@CM can enter the bone marrow and target the tumor cells owing to bone marrow homing and homologous targeting properties of the MM cell membrane. Once accumulating in the tumor site, ZIF‐8 decomposed under the acid microenvironment and released the encapsulated DOX and IR‐780. As a result, D/INPs@CM showed the best MM tumor eradication performance compared to D/INPs, without displaying noticeable systemic toxicity. All these features suggest that our biomimetic nanocarriers may have great potential for the precise and targeted therapy of MM and related other hematological malignancies.